The Sun Recorded Through History - Vaquero, J.M; Vázquez, M. (Astrophysics and Space Science Library,, 2009)
The Sun Recorded Through History is a text that reconstructs past solar activity based on information from historical documents, complementing studies using other techniques. Historical accounts describing phenomena related to solar activity, such as aurorae, sunspots, and corona observed during solar eclipses can be used as a proxy of solar activity in the past. These descriptions are reviewed, on the one hand providing primary material for the history of astronomy and, on the other, verifying or refuting current ideas concerning the time variability of the Sun on the scale of centuries. Documents predating the discovery of photography (around 1840) that contain information on these topics are highlighted, but modern drawings are also included. The lower temporal limit of study is set by the archaeoastronomy of prehistoric sources. In addition, the necessary background on the Sun is provided, with special emphasis on observing techniques and the influences of telescopes and the Earth's atmosphere on the data obtained from solar observations. This book contains over two hundred figures, many of which are reproductions of historical documents and hand drawings. It is an essential resource on the evolution of solar observations and will be of interest to students and researchers in solar physics, as well as astronomers and historians of science.